(3GdeGdjI GdYGeIs (3GdfabGJ GdYGeI(B- (3GdGjQGOGJ GdYGeI(B- (3GdejRGfjI GdYGeIs - (3HGNhjG(B, (3OQjSs ((3GdLRGFQs (3OGQ GdcJGH GdYQHjs, 2018)
(3JVefJ gPg GdOQGSI KdGKI aUhd eSHhbI HaUd JegjOj JVef GdGWGQ GdeaGgjej dYde GdeGdjI GdYGeI, HjfeG NUU GdaUd GdChd ddfabGJ GdYGeI, hajg JeJ OQGSI eaghe GdfabGJ GdYGeI hJbSjeGJgG, Ke GdbhGYOGdYGeI ddEfaGb GdYGe, aGdBKGQ GdGbJUGOjI ddfabGJ GdYGeI(B.(3HjfeG JVef GdaUd GdKGfj ddGjQGOGJ GdYGeI, hPdc ef NdGd HjGf eaghegG, Ke HjGf GjQGOGJ GdOhdI GdGbJUGOjI, HeG aj Pdc GdVQGFH hGdCMcGe GdefXeI dgG, hUhdG ddGjQGOGJ GdGSJKfGFjI ef bQhV YGeI hYedjGJ GdGUOGQ GdfbOj GdLOjO ceUOQ dJehjd GdejRGfjI(B. (3CeG GdaUd GdKGdK hGdCNjQ adbO NUU ddejRGfjI GdYGeI, HOAG HHjGf eaghegG, acjajI GYOGOgG, Ke GYJeGOgG, hUhdG deQMdI JfajPgG eY HjGf MGdGJ YLRgG hcjajI eYGdLI gPG GdYLR(B.s
Keywords: (3GdeGdjI GdYGeIs